Edukasi Pemanfaatan Pembuatan Kapsul Nanopartikel dari Tanaman Pinang (Areca catechu L) sebagai Upaya Terapi Adjuvan Pencegahan Schistosomiasis di Desa Alitipu Kecamatan Lore Utara, Kabupaten Poso, Sulawesi Tengah: Education on the Utilization of Making Nanoparticle Capsules from Areca Nut Plants (Areca catechu L) as an Adjuvant Therapy Effort for Schistosomiasis Prevention in Alitipu Village, North Lore District, Poso Regency, Central Sulawesi - Tandi, Joni; Magfirah, Magfirah; Kareba, Lexy; Handayani, Tien Wahyuni (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Alitupu Village, located in Napu Valley, North Lore District, Poso Regency, Central Sulawesi Province has the highest prevalence rate of schistosomiasis in humans, which is around 3.36%. Praziquantel as an antischistosomiasis causes side effects such as increased SGPT and SGOT, which is an obstacle in eradicating schistosomiasis, therefore developing natural resources with plants that have been proven to have properties as anthelmintic drugs, namely areca nut in the form of nanoparticles to maximize the biological availability of drugs given orally. This community service activity was carried out for 2 days in community groups and Gapoktan farmer groups with a socialization method by providing a pre-test, posters followed by a discussion session, questions and answers, and post-test and practice of making areca nut nanoparticles and making toilets followed by measuring satisfaction with community service by giving questionnaires to a total of 50 respondents. The results of the activity, the community was very enthusiastic and could increase their knowledge through the post-test. From the pretest calculation results of 24.4 and the posttest results obtained 86.8 people know how to prevent schistosomiasis. The results of the community satisfaction assessment showed that in general partners were satisfied with the activity by 92%. It can be concluded that this PKM activity is very beneficial for the people of Alitipu Village.